'In 1997 Nobody Had Heard of Windrush': The Rise of the 'Windrush Narrative' in British Newspapers. Issue 3 (2nd September 2019) - Peplow, Simon
ABSTRACT: The arrival of the Empire Windrush in 1948 has been cemented as a mythical central symbol for immigration in histories of modern Britain. This article traces the growth and impact of the 'Windrush-as-origins' myth through study of its depiction in British newspapers. It demonstrates the contradictions raised and seemingly ignored by such portrayals of migration, as well as the issues caused by the manufactured centrality of this constructed origin story for those who do not neatly fit into a simplistic narrative of the 'irresistible rise of multi-racial Britain' since World War II.